Targeted Inhibition of FTO Demethylase Protects Mice Against LPS-Induced Septic Shock by Suppressing NLRP3 Inflammasome - Luo, Jiahui; Wang, Faxi; Sun, Fei; Yue, Tiantian; Zhou, Qing; Yang, Chunliang; Rong, Shanjie; Yang, Ping; Xiong, Fei; Yu, Qilin; Zhang, Shu; Wang, Cong-Yi; et al. (Frontiers in Immunology, 2021)
Sepsis refers to the systemic inflammatory response syndrome caused by infection. It is a major clinical problem and cause of death for patients in intensive care units worldwide. The Fat mass and obesity-related protein (FTO) is the primary N6-methyladenosine demethylase. However, the role of FTO in the pathogenesis of inflammatory diseases remains unclear. We herein show that nanoparticle-mediated Fto-siRNA delivery or FTO inhibitor entacapone administration dramatically inhibited macrophage activation, reduced the tissue damage and improved survival in a mouse model of LPS-induced endotoxic shock. Importantly, ablation of FTO could inhibit NLRP3 inflammasome through FoxO1/ NF-κB signaling in macrophages. In conclusion, FTO is involved in inflammatory response of LPS-induced septic shock and inhibition of FTO is promising for the treatment of septic shock.